Original paperThe managed health care study for screening and early detection of colorectal cancer in Lodz urban population - Rysz, Jacek; Stolarek, Robert A.; Ostrowski, Stanisław; Kujawski, Krzysztof; Serwa-Stępień, Ewa; Irzmański, Robert; Barylski, Marcin; Błaszczak, Robert (Archives of Medical Science, 2005)
The quality improvement initiative was undertaken in parallel with prospective studies on the incidence and frequency of colorectal cancer (CRC) in urban population of Lodz, Poland. The study was conducted in four primary care providers with the support of academic medical institutions. The study population included the citizens of Lodz, both genders, aged 45 to 65. The study was divided in two stages; each conducted consecutively in 2003 and 2004. This prospective, two stage study included 3152 patients. After positive serial guaiac-based fecal occult blood tests, high CRC odds ratio based on per rectum examination and the standardized questionnaire data 47.8% out of 1648 and 18.9% out of 1504 initially enrolled patients were enrolled into the extended diagnostic stage of the study within the consecutive years, respectively. CRC was found in 0.9% and 0.54% patients, respectively and the diagnosis of CRC was confirmed with histopathological tests. Colorectal diseases other than CRC were found in 23.1% and 11.2% of the study subjects, respectively. It is crucial to design and implement follow-up studies for those among our study subjects at high risk of CRC who finished the current study even without an unfavourable diagnosis or risk rating.